Et informationsvidenskabeligt serviceeftersyn af Medicin.dk - Simonsen, Henrik Køhler (Nordiske Studier i Leksikografi, 2012)
This article discusses information science and modern metalexicography, arguing that both disciplines share many characteristics. On the basis of this theoretical discussion a new information-science model is introduced, and it is argued that this model encompasses the six most important dimensions in modern information science and metalexicography. The analysis model is then applied to Medicin.dk, which is one of Denmark’s leading websites supplying health and medicinal information. The analysis of Medicin.dk is based on empirical data from a questionnaire survey involving 3,813 respondents, an interview survey comprising 11 doctors and other health care professionals, and two workshop surveys comprising 17 health care professionals. The empirical data also include data from a usability survey involving 8 citizens with different backgrounds. The analysis of the empirical data and the design and content analysis of Medicin.dk showed that the social relational needs of patients and relatives were not sufficiently met by the non-professional section of Medicin.dk called min.medicin.dk. Finally, a conceptual framework for the application of social media in a reference work such as Medicin.dk is proposed, and it is argued that social media facilitate the satisfaction of the social-relational needs of patients and relatives.